Challenges faced by educators in the implementation of Flipped Classroom - Radza, Rubini (Department of Applied Linguistics, FBSB, Universitas Negeri Yogyakarta, 2023)
This study intends to provide a review on the challenges faced by educators in the implementation of flipped classroom and ways to overcome the challenges. This review paper was written based on interpretations done on previous literature covering multiple aspects in the field such as roles or ability of teacher, students and area of study. Mainly, it focuses on the limitations in terms of time management, technological necessity and facilities, heavy demand on teacher functionality, interests and involvement of students which are handled by the teachers. This paper determines the existing demands of this approach and suggests the measures to be taken by the educators who are enthralled to embrace and practice this concept in classroom in the time that is to come. In general, this article provides essential information about the nature and difficulties to implement the flipped classroom approach, its limitations, the extent of expectations on teachers and some useful suggestions to overcome the issues.